2019
DOI: 10.1002/dmrr.3151
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence of gestational diabetes and perinatal outcomes in Catalonia, Spain, 2006 to 2015: the Diagestcat Study

Abstract: Background:No recent epidemiologic studies on gestational diabetes mellitus (GDM) have been conducted in Spain. The present study aimed to explore trends in the prevalence of GDM and ascertain whether the risk of adverse perinatal outcomes changed between 2006 and 2015 in Catalonia. Methods:In this population-based study, all hospital admissions for singleton births in Catalonia for the period 2006 to 2015 were collected from the Spanish Minimum Basic Data Set. Cases of GDM were identified from hospital delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 37 publications
5
28
0
8
Order By: Relevance
“…Urinary tract infection (n = 3; 3.4%), hypoglycemia (n = 2; 2.27%), polyhydramnios (n = 2; 2.27%), vaginitis (n = 4; 4.54%), pre-eclampsia (n = 4; 4.54%) and chronic fetal distress with IUGR (n = 2; 2.27%) were the secondary outcomes identified during prenatal followups. These findings are compatible with data available in the medical literature [28][29][30][31][32]34,35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Urinary tract infection (n = 3; 3.4%), hypoglycemia (n = 2; 2.27%), polyhydramnios (n = 2; 2.27%), vaginitis (n = 4; 4.54%), pre-eclampsia (n = 4; 4.54%) and chronic fetal distress with IUGR (n = 2; 2.27%) were the secondary outcomes identified during prenatal followups. These findings are compatible with data available in the medical literature [28][29][30][31][32]34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Diabetic pregnant women presented the following primary outcomes: fetal and neonatal mortality (1.8%), macrosomia (6.81%), prematurity (16.6%) and hospitalization in neonatal ICU (9 %). All these findings presented lower rates than the ones reported in many other services [32][33][34][35]. There was an association between diabetes and prematurity and between diabetes and hospitalization in neonatal ICU (p < 0.05).…”
Section: Discussionmentioning
confidence: 56%
“…Lavery et al reported about 5.5% increase in GDM prevalence in the USA over a 20-year period from 1990 to 2010 [3]. A study in Spain examining the trend of GDM prevalence showed an increase of 4.8% over a period of 9 years from 2006 to 2015 [4]. According to the International Diabetes Federation, South East Asia had the highest prevalence of GDM with 26.6% followed by Middle East/North Africa (18%), Europe (14%) and Africa (9.5%) [2].…”
Section: Prevalence Worldwide and The Trends Over The Past Decadementioning
confidence: 98%
“…У третьому мета-аналізі (Behboudi-Gandevani С, 2019) [4], що включав 51 популяційне дослідження (5439476 вагітних жінок), загальна поширеність ГЦД, незалежно від референтних значень скринінгу, становила 4,4% з найвищою частотою в Східній Азії та найменшою -в Австралії (відповідно, 11,4% і 3,6%). За даними окремих наукових джерел поширеність цукрового діабету (ЦД) у Франції становить 7,24% [5], в Іспанії -4,8% [6], у США -15% [7] та в Австралії -13% [8].…”
Section: вступunclassified